2020
DOI: 10.3389/fgene.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Normalization Methods on Single-Cell RNA-seq Data: An Empirical Survey

Abstract: Data normalization is vital to single-cell sequencing, addressing limitations presented by low input material and various forms of bias or noise present in the sequencing process. Several such normalization methods exist, some of which rely on spike-in genes, molecules added in known quantities to serve as a basis for a normalization model. Depending on available information and the type of data, some methods may express certain advantages over others. We compare the effectiveness of seven available normalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…In COVID-19, neutrophil activation/degranulation is the largest gene signature in blood cells [ 89 ] predicting disease severity [ 90 ] and mortality [ 91 ]. An increasing number of reports have identified a high neutrophil to lymphocyte ratio to be associated with severe COVID-19 [ 92 , 93 ].…”
Section: Introductionmentioning
confidence: 99%
“…In COVID-19, neutrophil activation/degranulation is the largest gene signature in blood cells [ 89 ] predicting disease severity [ 90 ] and mortality [ 91 ]. An increasing number of reports have identified a high neutrophil to lymphocyte ratio to be associated with severe COVID-19 [ 92 , 93 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has been extensively studied and addressed in a number of ways: normalization, regression of unwanted sources of variation, etc. [24, 25, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Normalization using regularized negative binomial regression effectively eliminates technical differences due to different sequencing depth without inhibiting biological heterogeneity. A previous study [36] compared seven scRNA-seq data normalization methods with regard to reduction of noise or bias, and found that each of these methods was suitable to normalize specific types of data for further downstream analysis.…”
Section: Normalizationmentioning
confidence: 99%